2020
DOI: 10.1002/osp4.452
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of behavioral interventions and behavior change techniques for reducing soft drink intake in disadvantaged adolescents: A systematic review and meta‐analysis

Abstract: Reducing sugar-sweetened beverage (SSB) intake is an important dietary target, especially among socioeconomically disadvantaged ethnic minority adolescents. This review and meta-analysis evaluated the effectiveness of behavioural interventions aiming to reduce SSB intake in socioeconomically disadvantaged ethnic minority adolescents and examined which behaviour change techniques (BCTs) were most effective. A systematic search was conducted using the PRISMA criteria. Quality assessments were done using the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 72 publications
(563 reference statements)
5
15
0
Order By: Relevance
“…Gregorio-Pascual & Mahler, 2020 ). On the other hand, interventions aimed at improving individuals’ self-regulatory capacity and/or developing healthy drinking habits normally use various behavior change techniques (BCTs), such as feedback, goal-setting, self-monitoring, and so on (Shagiwal et al, 2020 ). Previous studies also showed a signifiant reduction of SSB consumption for intervention focused on self-regulatory capacity and habit among adolescents (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Gregorio-Pascual & Mahler, 2020 ). On the other hand, interventions aimed at improving individuals’ self-regulatory capacity and/or developing healthy drinking habits normally use various behavior change techniques (BCTs), such as feedback, goal-setting, self-monitoring, and so on (Shagiwal et al, 2020 ). Previous studies also showed a signifiant reduction of SSB consumption for intervention focused on self-regulatory capacity and habit among adolescents (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…46 Several public health interventions have been conducted aiming to reduce the consumption of SSBs. 9,49,84 The most commonly discussed public health strategies aiming to decrease the consumption of SSBs are summarized in Table 1. In this review, we described implemented taxation measures and their impact in sales and in preventable cases of disease and death, marketing regulations applied to children and adolescents, and ultimately the intention of application of a single FOP labeling system in all countries, with the goal of increasing consumers' food literacy.…”
Section: Critical Analysis and Conclusionmentioning
confidence: 99%
“…Several public health interventions have been conducted aiming to reduce the consumption of SSBs 9,49,84 . The most commonly discussed public health strategies aiming to decrease the consumption of SSBs are summarized in Table 1.…”
Section: Critical Analysis and Conclusionmentioning
confidence: 99%
“…Interventions that address multiple levels of the socialecological model and incorporate systems thinking are recommended to improve health outcomes, especially among vulnerable populations [81]. A systematic review and metaanalysis found studies using self-regulatory behavior change techniques, including feedback, goal-setting, action planning, self-monitoring, and problem-solving, helped to reduce SSB intake among socioeconomically disadvantaged adolescents from ethnic minorities, but overall, the behavioral interventions were not very effective [82]. The researchers noted that more high-quality studies investigating behavioral interventions in disadvantaged youth are needed and that future studies should design interventions that utilize strategies tailored to these groups [82].…”
Section: Implications For Public Health and Practicementioning
confidence: 99%